Assessment of Soil Shear Strength Parameters: Insights from Direct Shear and Direct Simple Shear Testing - Kalumba, Denis; Babalola, Zainab; Aneke, Frank; Chebet, Faridah; Sobhee-Beetu, Laxmee (Civil Engineering Journal, 2025)
The direct shear test is widely used to determine shear strength parameters ( ) of soil. However, its validity has been questioned due to several issues, such as uneven stress distribution, the creation of a predetermined failure plane, lateral constraints, difficulties in controlling drainage conditions, and limitations in measuring pore water pressure, which is essential for understanding soil behaviour under different conditions over time. This study addresses these concerns by comparing the shear strength parameters obtained from a direct shear test (DST) and a direct, simple shear test (DSST). To further explore these issues, a fully automated universal shear device was used to perform shear tests on clay, sand, and composite soil (clay + sand), covering both consolidated and shear phases of DST and DSST. Specimens were fabricated at their optimal moisture content, and the composite soil was developed by mixing clay with sand in proportions of 10%, 25%, 50%, and 75% of the mass of sand. This research aims to clarify the relationship between these two testing methodologies through comprehensive testing and to enhance the knowledge of the principal mechanism of the 2 tests. The findings revealed that the DST yielded higher shear strength values than the DSST results. It was also observed that the friction angle of sand specimens generally decreased with the addition of clay for both tests. Additionally, the the kaolinite soil in DST and DSST, decreased in the sand as the clay contents increased.